Empowerment of UP2K Cadres through the Sharia Financial Literacy Program as an Effort to Strengthen MSMEs in Sajen Village, Pacet District, Mojokerto Regency - Husen, Mohamad Nur; Ahmad, Zakiyyah Ilma; Shiddiq, Jafar; Wahid, Abdul; Umam, Syafiul; Maulana, Kevin; Nasirin, Muhammad Khoirun (Edumedia Solution, 2025)
The Student Creativity Program (PKM) aims to empower Family Income Improvement Enterprise (UP2K) cadres through a sharia financial literacy program to strengthen the capacity of Micro, Small, and Medium Enterprises (MSMEs). Problems faced by MSMEs at the village level are often related to a lack of understanding of financial management, particularly in the context of sharia finance that aligns with the religious values ​​of the local community. Through an educational and participatory approach, this activity involves training, mentoring, and a simple application-based sharia financial recording simulation. Implementation methods include needs mapping, developing a sharia financial literacy module, training cadres of the Sajen Village UP2K, and monitoring and evaluating the impact on strengthening the fostered MSMEs. The results of the activity show a significant increase in the cadres' understanding of sharia financial concepts and practical financial recording skills. This program is expected to become a sustainable empowerment model that encourages economic independence based on sharia values ​​at the grassroots level.